2022
DOI: 10.3389/fcell.2022.842214
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of YAP1 Promotes the Resistance to Chemo- and Targeted Therapy in FLT3-ITD+ AML Cells

Abstract: The FLT3-ITD mutation occurs in about 30% of acute myeloid leukemia (AML) and is associated with poor prognosis. However, FLT3 inhibitors are only partially effective and prone to acquired resistance. Here, we identified Yes-associated protein 1 (YAP1) as a tumor suppressor in FLT3-ITD+ AML. YAP1 inactivation conferred FLT3-ITD+ AML cell resistance to chemo- and targeted therapy. Mass spectrometric assay revealed that DNA damage repair gene poly (ADP-ribose) polymerase 1 (PARP1) might be the downstream of YAP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“… 41–43 Downregulated expression of YAP1 accelerates resistance to chemotherapy and targeted drugs in FLT3-ITD + AML cells and docetaxel resistance in prostate cancer. 44 , 45 In our study, we confirmed that miR-375-3p targets YAP1. Our further research showed that circSH3PXD2A promotes YAP1 expression by sponging miR-375-3p and suppresses the chemoresistance of SCLC in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 81%
“… 41–43 Downregulated expression of YAP1 accelerates resistance to chemotherapy and targeted drugs in FLT3-ITD + AML cells and docetaxel resistance in prostate cancer. 44 , 45 In our study, we confirmed that miR-375-3p targets YAP1. Our further research showed that circSH3PXD2A promotes YAP1 expression by sponging miR-375-3p and suppresses the chemoresistance of SCLC in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 81%
“…YAP plays a critical role in the pathogenesis of malignancies and it was recently shown to mediate resistance to chemotherapy in AML cells [ 18 , 19 ]. YAP is associated with cell growth and adhesion, lipogenesis, and numerous G-protein–coupled receptor ligands [19] .…”
Section: Resultsmentioning
confidence: 99%
“…While these recent results clearly demonstrate that recombinant HDAC10 has negligible or low lysine deacetylase activity in vitro , some reports support earlier findings that HDAC10 catalyzes protein deacetylations. For instance, HDAC10 catalyzes the deacetylation of non-histone proteins including Hsc70/Hsp70 ( 98 ), EWSR1 ( 99 ), YAP1 ( 100 ), MSH2 ( 94 ) and hSSB1 ( 101 ). Conceivably, HDAC10 may associate with other HDACs to indirectly deacetylate proteins in living cells.…”
Section: Discussionmentioning
confidence: 99%